Are climate- and peace and security-related policies coherent? A policy coherence analysis for climate security - Schapendonk, Frans; Madurga Lopez, Ignacio M.; Savelli, Adam; Sarzana, Carolina (2022)
The impacts of climate change and variability will likely be experienced in different and uneven ways depending on the different extents to which societies – and the communities within them – are exposed, vulnerable, or possess the adaptive capacity to mitigate said impacts. Certain countries, such as those located near the equator or the poles, are exposed to a rapidly changing climate to a greater degree than other countries. Furthermore, countries whose economies are highly dependent on climate-sensitive resources and sectors and that face challenges in diversifying their economic base are inherently more vulnerable to climate-induced perturbations (Feitelson & Tubi, 2017). These forms of exposure can be compounded by persistent or periodically high levels of fragility – defined by the World Bank (2011) as periods when states or institutions lack the capacity, accountability, or legitimacy to mediate relations between citizen groups and between citizens and the state – which can in turn undermine the extent to which societies as a whole and certain groups within them possess the adaptive capacity to manage, absorb or mitigate climate risks. Communities that are highly dependent on climate-vulnerable livelihoods and sectors, face socio-economic and political marginalisation (therefore possessing little scope or capacity for diversification), or that are located in unstable and conflict-prone environments are far more likely to experience tangibly destabilising climatic impacts than others. As a consequence of the uneven landscape upon which climate impacts play out, climate change is therefore likely to set in motion or accelerate any number of different existing processes of change simultaneously - yet in qualitatively different ways.